2014
DOI: 10.1111/ced.12305
|View full text |Cite
|
Sign up to set email alerts
|

Nodular localized primary cutaneous amyloidosis: a bullous variant

Abstract: Primary cutaneous amyloidosis describes a group of disorders in which amyloid is deposited in the skin without evidence of systemic involvement. Nodular localized primary cutaneous amyloidosis (NLPCA) is a rare form of these skin-restricted amyloidoses. We present an unusual case of NLPCA in a 51-year-old man, who had clinical and histopathological evidence of subepidermal bullous formation, a unique feature in NLPCA. The possible pathogenesis of this change is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The case in our study presented with a rare bullous-like nodular variant. LaChance et al reported a bullous variant of PLCNA in a 51-year-old man on his third right toe [ 10 ]. PLCNA mainly occurs between the ages of 40 and 60, with the same proportion in men and women [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The case in our study presented with a rare bullous-like nodular variant. LaChance et al reported a bullous variant of PLCNA in a 51-year-old man on his third right toe [ 10 ]. PLCNA mainly occurs between the ages of 40 and 60, with the same proportion in men and women [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient presented with a typical solitary firm waxy plaque. Rarer variants include nodular primary amyloidosis with extensive involvement, bullous and genital variants 6–8…”
Section: Discussionmentioning
confidence: 99%
“…Immunostains reveal cytokeratin positivity, indicating that the material is derived from keratinocytes. 10 PLCNA occurs in the sixthseventh decades of life with no sex predilection. 2,4 The primary localized form of cutaneous nodular amyloidosis, PLCNA, is rare and manifests as waxy yellowish to red-brown plaques, papules, or nodules on the legs, head, trunk, arms, and genitalia.…”
Section: Discussionmentioning
confidence: 99%